Impacts and effectiveness of negative political advertising in Czech environment - Svetlik, Jarolav (Political Preferences, 2016)
Negative political advertising and its effectiveness has always been concern of not only political scientists, but also sociologists and marketing experts. This specific form of advertising is also increasingly used in the Czech political environment. The author focused on the answers to the questions, what are the effects of this form of political advertising from the perspective of persuasive linear models, whichis actuallycognition, emotion and conative/voting behavior. Based both on international research carried out in this area and facts from Czech republic, he notes that voters perceive this form of advertising as one that offers them more information, attract a greater degree of attention and more trust than in the case of positive advertising. From emotional effects point of view, this form of political advertising is often followed by disgust, fear and other negative reactions. Which are, however, strong appealsthat subsequently bring some negative effects in voter`s conative/behavioral activities. These include in particular the reluctance to vote, negative public sentiment and escalating political cynicism. In the evaluation of the effectiveness of negative political campaigns shouldalso be taken into account their cultural environment. What could be effective in the US may not be very effective in countries with different cultural values given by their historical development and by existingcultural dimensions of these countries. Key words: political campaign, negative political campaign, political advertising, negative advertising